Nanoparticulate Drug Delivery: Ezetimibe and Enteric-coated Atorvastatin in Hard Gelatin Capsules - Subramanian, S. (Asian Journal of Pharmaceutics (AJP), 2023)
Aims: Atorvastatin (ATV) and ezetimibe (EZT), being BCS class II drugs, are used to treat dyslipidemia. In this study, the formulation of hard gelatin capsule containing a fixed dose combination of EZT and enteric-coated ATV enhances the rate of dissolution through solubility using nanoprecipitation method. Materials and Methods: ATV nanoparticles (NPs) and EZT NPs were prepared using polyvinyl pyrrolidine k-30 as an amorphous carrier in various drug to polymer ratios. The formulated NPs of both drugs were characterized for their particle size, zeta potential, and polydispersity index, and for optimized formulation entrapment efficiency and scanning electron microscopy (SEM) which were determined. AT VNPs were coated using ethyl cellulose and were characterized. Flow characteristics of enteric-coated ATV and EZT NPs were assessed and filled into empty hard gelatin capsules. The hard gelatin capsule containing powders of EZT and enteric-coated ATV NPs was also evaluated for weight variation, disintegration time, in vitro drug release, and drug content. Results and Discussion: The particle size for the formulation of ATV NP and EZT NP was found to be 470.5 nm and 469.2 nm, respectively. The morphology of the best formulation for both NPs, determined using SEM, indicates that they are spherical in shape. The in vitro release studies of enteric-coated ATV NPs show 5% release in an acidic pH for 2 h followed by 92.89% release in a basic pH at the end of 3 h before loading into hard gelatin capsules to prove that there was no release of ATV NPs in acidic medium. Hard gelatin capsules containing enteric-coated ATV NPs and EZT NPs showed drug release of 98% and 99% within 45 min. Conclusion: The hard gelatin capsule of enteric-coated ATV NPs and EZT NPs showed better drug release when compared to the marketed formulation.